Aplikasi Braille dalam Penulisan Al-Qur’an Kajian atas Mushaf Standar Braille Indonesia - Jaeni, Ahmad (SUHUF, 2013)
This article will examine the applicationof Braille in the writing of the Qur'an, especially those being applied in the Mushaf of Braille Standard. The Mushaf of Braille Standard is an edition which is specifically designed for the visually impaired Indonesian Muslims. This study aims at determining of how the Braille as writing system is applied in the writing of the Qur'an which is actually written in the words and Arabic language. The results of this study are expected to reveal the common characteristics in the application of the Braille in Mushaf of Braille Standard.